Disseminating Agricultural Research on Radio - Raymond W. Barclay Jr. (Journal of Applied Communications, 1986)
Since the 1930s, studies have been conducted throughout the country to evaluate the effectiveness of Extension radio programs, commonly called Farm and Home radio (Crile, 1949).